Diversity of fungal pathogens isolated from diseased goosegrass (Eleusine indica) as potential biological control against goosegrass - Fakri, Muhammad Aiman; Sapak, Zaiton; Ahmad Hamdani, Muhammad Saiful; Chuah, Tse Seng (Friends Science Publishers, 2023)
Several studies have been undertaken on the possible use of fungal pathogens for biological control of goosegrass (Eleusine indica), but the diversity of fungal pathogens isolated from diseased E. indica infesting various crops has received little attention. The objectives of this study were to 1) isolate and identify fungal pathogens from diseased E. indica that infected numerous food crops and 2) assess the pathogenicity of the isolated fungal pathogens against diseased E. indica in the greenhouse. On the basis of morphological characteristics and genetic analysis, Fusarium chlamydosporum, F. proliferatum, Bipolaris bicolor, Curvularia senegalensis, and Lasiodiplodia theobromae were successfully isolated and identified from diseased E. indica growing around mango, oil palm, wax apple, maize, and paddy fields, respectively. Within ten days of evaluation, the pathogenicity of the fungal isolates varied, with B. bicolor, L. theobromae, and F. proliferatum exhibiting high values of area under the disease progression curve (AUDPC) ranging from 274 to 339. These findings indicate that fungal pathogens are potential candidates for use as biological control agents against E. indica.